2018
DOI: 10.1590/0004-282x20180122
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis and classical music: the great composers and “The Great Imitator”

Abstract: Throughout history, neurosyphilis has victimized many people, including classical composers, with a wide range of clinical presentations. Methods: Six articles with descriptions of composers with possible neurosyphilis were reviewed. Results: Neurosyphilis is a possible diagnosis for composers like Beethoven, whose progressive hearing loss influenced his career, culminating in complete deafness. In his autopsy, cochlear nerve atrophy and cochlear inflammation were described. Donizetti developed behavioral ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…From Bedrich Smetana, who incorporated the sounds of his neurological disease into a composition for string quartet 8 , to Oliver Sacks' insightful writings on amusia from a medical perspective 9 , few relationships are more fruitful than that of Music and Medicine. In his lecture, Aloysio de Castro further reinforced the bond, providing us not only with the typical analysis of the artist's death but also an intense appraisal of his life and the spiritual aspects of the performance of Chopin's music.…”
Section: Resultsmentioning
confidence: 99%
“…From Bedrich Smetana, who incorporated the sounds of his neurological disease into a composition for string quartet 8 , to Oliver Sacks' insightful writings on amusia from a medical perspective 9 , few relationships are more fruitful than that of Music and Medicine. In his lecture, Aloysio de Castro further reinforced the bond, providing us not only with the typical analysis of the artist's death but also an intense appraisal of his life and the spiritual aspects of the performance of Chopin's music.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the missing typical anamnestic and autoptic findings regarding the signs of syphilis in Beethoven, a more recent examination of a ringlet of the composer in 2000 demonstrated that there was no detectable mercury in Beethoven's hair which makes syphilis therapy with mercury unlikely [26]. In opposition to these arguments against syphilis as the cause of Beethoven's hearing impairment, the syphilis diagnosis has gained interest again in the medical literature of the twenty-first century by up to now four authors with medical specialization in infectiology, neurology, and psychiatry favouring this aetiology anew [27][28][29][30]. Overall, syphilis is still one of the aetiologies which has most often been accused of being the cause of Beethoven's hearing loss by medical publishers over the past 100 years.…”
Section: Discussionmentioning
confidence: 99%
“…A catastrophic neurological disease, whose prognosis is today almost as dire as it was in the Victorian age, led to an untimely death, which, in turn, inspired an outstanding literary work. As previously argued by the same author [50], neurological diseases and the suffering borne from them, though often conflated solely with limitations on the artistic output of ill or grief-stricken artists, may also serve as a source of change, helping the definition of a new artistic voice or style, and, thus, indirectly serve as a pivotal force to higher artistic aspirations and creations.…”
Section: “We Close With All We Loved”: Conclusionmentioning
confidence: 99%